Preliminary research on seed yield and nutritional traits of desi chickpea (Cicer arietinum L.) grown in Central Italy in spring sowing - Paolo CASINI (Acta Agriculturae Slovenica)
In Italy, chickpea (Cicer arietinum L.) cultivation of the kabuli type is predominant, with local landraces of the desi type, including the Apulian black chickpea, occurring almost exclusively in the south. However, increasing interest in the desi type on the part of farmers and consumers is based on the nutritional properties constituting a niche area in the market health sector. Information pertaining to both field evaluation of desi chickpea in Central Italy and the chemical composition is scarce. Therefore, the aim of this preliminary research was to evaluate the agronomic performance to the agroclimatic environment of Central Italy of thirteen lines of desi chickpea accessions of different origins, as well as the ‘Apulian Black Chickpea’ (ABC). Accessions were sown on March 21 in 2019, without the use of irrigation. The principle qualitative characteristics, namely protein content and raw fiber were determined. Yield was excellent for 57 % of the accessions, some of which exceeded 3.0 t ha-1 with the maximum value of 4.1 t ha-1 recorded for ‘PI598080’ (brown seeds of Indian origin). ‘W617611’ (black seeds of Turkish origin) was the earliest flowering line at 74 days after sowing, permitting this accession to escape the onset of drought and high temperatures. Additional early flowering lines included ‘PI533676’ (black seeds of Ukrainian origin) and ‘PI567850’ (black seeds of Pakistani origin), respectively. Plant structure relating to the average height of the plants (47.0 cm), the height of the first pod (30.8 cm) and the number of branches per plant (2.6) rendered most accessions suitable to combine harvesting, an indispensable prerequisite in the maintenance of an economically sustainable crop. The average protein content was 22.7 % with maximum values exceeding 24 % (‘PI572520’ - black seeds of Syrian origin -, ‘W617614’ - black seeds of Turkish origin - and ‘PI572850’). The fiber content was very heterogeneous ranging from 4.6 % to 12.0 %.The present study provides the basis towards the future introduction of desi chickpea in Central Italy, with the potential for sustainable yield and quality.